Characterization of ROP18 alleles in human toxoplasmosis (2014)
The role of the virulent gene ROP18 polymorphisms is not known in human toxoplasmosis. A total of 320 clinical samples were analyzed. In samples positive for ROP18 gene, we determined by an allele specific PCR, if patients got the upstream insertion positive ROP18 sequence Toxoplasma strain (mouse avirulent strain) or the upstream insertion negative ROP18 sequence Toxoplasma strain (mouse virulent strain). We designed an ELISA assay for antibodies against ROP18 derived peptides from the three major clonal lineages of Toxoplasma. 20 clinical samples were of quality for ROP18 allele analysis. In patients with ocular toxoplasmosis, a higher inflammatory reaction on eye was associated to a PCR negative result for the upstream region of ROP18. 23.3%, 33% and 16.6% of serums from individuals with ocular toxoplasmosis were positive for type I, type II and type III ROP18 derived peptides, respectively but this assay was affected by cross reaction. The absence of Toxoplasma ROP18 promoter insertion sequence in ocular toxoplasmosis was correlated with severe ocular inflammatory response. Determination of antibodies against ROP18 protein was not useful for serotyping in human toxoplasmosis.